2013
DOI: 10.1063/1.4802585
|View full text |Cite
|
Sign up to set email alerts
|

Communication: Chemical bonding in carbon dimer isovalent series from the natural orbital functional theory perspective

Abstract: A new near-linear scaling, efficient and accurate, open-shell domain-based local pair natural orbital coupled cluster singles and doubles theory

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 37 publications
3
37
0
Order By: Relevance
“…However, it is worth noticing that both set of orbitals represent unique correlated one-electron pictures of the same energy minimization problem, ergo, they complement each other in the analysis of the molecular electronic structure [31] in a manner that is promising, albeit perhaps not fully understood. [32] There is much to be done to improve the method. In particular, it is necessary to include the missing interactions, and it was shown above that a multireference PT that uses the generating wavefunction as a reference, is one of the possible solutions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is worth noticing that both set of orbitals represent unique correlated one-electron pictures of the same energy minimization problem, ergo, they complement each other in the analysis of the molecular electronic structure [31] in a manner that is promising, albeit perhaps not fully understood. [32] There is much to be done to improve the method. In particular, it is necessary to include the missing interactions, and it was shown above that a multireference PT that uses the generating wavefunction as a reference, is one of the possible solutions.…”
Section: Discussionmentioning
confidence: 99%
“…These PNOF5 canonical molecular orbitals result to resemble closely the delocalized Linear Combination of Atomic Orbitals molecular orbitals. [29][30][31][32] Nevertheless, it is worth recalling that both the natural and canonical PNOF5 orbitals are correlated orbitals in the sense that they carry on the essentials of the electron correlation effects in a similar way as those obtained within the correlated orbital theory. [33] Furthermore, the analysis of the natural PNOF5 geminals has shown that they satisfy the Casida's N-representability condition [34] for the eigenvalues of the reconstructed 2-RDM.…”
Section: Introductionmentioning
confidence: 99%
“…It is useful therefore, that such approximations should satisfy known constraints. Examples include [21] REVIEW WWW.Q-CHEM.ORG 60) and…”
Section: Correlation Aspects As Consequences Of the Pauli Potentialmentioning
confidence: 99%
“…[54][55][56] The one-electron picture provided by PNOF5 is really very appealing since its orbitals agree closely with the orbitals provided by the valence bond method and with those obtained by a standard molecular orbital calculation. [57][58][59][60] PNOF5 is probably the first NOF obtained by both bottom-up and top-down methods. [49,61] This result is remarkable since the functional N-representability problem is solved, which implies that PNOF5 can be derived from a wavefunction that is antisymmetric in N particles.…”
Section: The Functional Pnof5(n C )mentioning
confidence: 99%
“…
be comparable to accurate quantum chemistry methods in many cases [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. So far this is the only natural orbital functional (NOF) that has been obtained by top-down and bottom-up methods [19].
…”
mentioning
confidence: 99%